Sino-Cuban relations from 1964 to 1995: conflict and reconciliation - Kruarattikan, Sitthiphon (Asia in World Politics: Past, Present, and Future, 2021)
The aim of this chapter is to examine bilateral relations between Cuba and China since the establishment of diplomatic ties in 1960 till the 80s when both two countries strengthened cooperation. The paper shows reasons for conflict between Cuba and China which started in the mid-60s emphasizing crucial moments like “rice war” and termination of party relations. It also analyzes incentives which led to the process of reconciliation and normalization of bilateral ties. The author underlines the role of Sino-Soviet relations and Sino-American rapprochement as a crucial factors which impacted relations between Beijing and Havana but also argues that China has never seen Cuba as a security threat but rather target for “moral attack” to deprecate Moscow.